2004
DOI: 10.1200/jco.2004.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy With Gemcitabine Plus Oxaliplatin in Patients With Intensively Pretreated or Refractory Germ Cell Cancer: A Study of the German Testicular Cancer Study Group

Abstract: Gemcitabine plus oxaliplatin demonstrates antitumor activity with acceptable toxicity in heavily pretreated patients with relapsed or cisplatin-refractory GCT, and may offer a chance of long-term survival for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 21 publications
3
56
0
2
Order By: Relevance
“…Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008). Using ProCISE, we also demonstrated that the administration of carfilzomib inhibits proteasome subunit occupancy in bone marrow–derived tumour cells.…”
Section: Discussionmentioning
confidence: 80%
“…Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008). Using ProCISE, we also demonstrated that the administration of carfilzomib inhibits proteasome subunit occupancy in bone marrow–derived tumour cells.…”
Section: Discussionmentioning
confidence: 80%
“…A number of publications are now available describing experience with single agents (Motzer et al, 1994;Bokemeyer et al, 1996Bokemeyer et al, , 1999Sandler et al, 1998;Einhorn et al, 1999;Kollmannsberger et al, 2002a b) or drug combinations (Miki et al, 2002;Hinton et al, 2002;Madani et al, 2003;Kollmannsberger et al, 2004) in patients with end-stage and cisplatin-refractory disease. Paclitaxel, gemcitabine and oxaliplatin have been evaluated as single agents, and the combinations paclitaxel and gemcitabine (Hinton et al, 2002), oxaliplatin and gemcitabine (Kollmannsberger et al, 2004), cisplatin and irinotecan (Miki et al, 2002) and cisplatin and epirubicin (Madani et al, 2003) as combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious need to improve these results has yielded two different strategies: the increasing use of new drugs with paclitaxel (Motzer et al, 1994;Bokemeyer et al, 1996;Sandler et al, 1998), gemcitabine (Bokemeyer et al, 1999;Einhorn et al, 1999), oxaliplatin (Kollmannsberger et al, 2002a), irinotecan (Kollmannsberger et al, 2002b;Miki et al, 2002) and epirubicin (Madani et al, 2003) currently under evaluation as single agents or in combination (Hinton et al, 2002;Miki et al, 2002;Kollmannsberger et al, 2004), and the development of high-dose chemotherapy, particularly since the advent of autologous stem cell rescue and growth factor support (Motzer et al, 1992(Motzer et al, , 2000aBeyer et al, 1997;Bhatia et al, 2000;Rosti et al, 2002;Kollmannsberger et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs having efficacy include oral etoposide, paclitaxel, gemcitabine, oxaliplatin or combinations of these drugs. 185 While infrequent, some patients being treated in the third-line setting may have long-term disease control or cure in particular if the tumour lesions can be completely resected. 184 …”
Section: Multiply Refractory Patientsmentioning
confidence: 99%